FROM INPUT TO OUTPUT: THE IMPACT OF INTERACTION IN ENGLISH AS A SECOND LANGUAGE ACQUISITION IN A MANDARIN-SPEAKING ENVIRONMENT - Rhamadanty, Winda Ayu Utami (Lembaga Jurnal FKIP Universitas Bosowa, 2024)
This qualitative study investigates the effect of interaction on ESL acquisition in a Mandarin-speaking environment in terms of comprehension, output confidence, and linguistic accuracy. Data collection was done through semi-structured interviews, classroom observations, and reflective journals involving Mandarin-speaking ESL learners. The findings show that interactive learning environments significantly enhance comprehension by enabling learners to negotiate meaning and clarify complex linguistic forms. Besides, the regular activity of interactive tasks enhances learners' confidence and precision in complex language production. Scaffolding by the teacher and corrective feedback, especially through methods like recasting and elicitation, further fine-tune grammatical accuracy and pronunciation to overcome specific problems of Mandarin-speaking learners. The study emphasizes interaction as a necessary bridge between input and output, therefore offering practical insights for ESL instruction in linguistically distinct environments.